Initiatives for the quality of medical simulation in the training of nurses - Studnicka, Katarzyna; Zarzycka, Danuta (Journal of Education, Health and Sport, 2019)
Introduction. In the training of nurses, simulation is used more and more often as an educational tool. For that purpose, various means and tools of simulation are employed, starting with simple trainers, which have been in use for quite a long time, through complex in structure and more and more physiologically and informatically advanced high-fidelity simulators placed in a realistic virtual environment to trained people (so called standardised patients). The addressee of the educational actions, assuming an active role, is a student, but it is the teacher with a special training in conducting this type of courses that is the coordinator of such actions. Purpose. Presentation of selected initiatives for the quality of medical simulation in training nurses. Method. Unsystematic review of literature, based on the thematic selection of articles, with a preference for the studies constituting a systematic review of works published in the last 14 years.Results.All the organizations mentioned below support and shape globally the development of medical simulation in the training of nurses. It is worth getting familiar with their mission and standards as they can help to develop medical simulation and educate the students of nursing at the best possible level so as to master not only the basic skills, but also those related to the communication within a team or decision making. Summary. Simulation has existed for centuries, but only recently has it started to have a big impact on healthcare. A need exists for the change in the training of nurses to facilitate the transfer of theoretical knowledge for the student into the clinical context and develop the necessary personal competences, which can be provided for by high-fidelity simulation.